2013
DOI: 10.1002/embr.201338025
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin in the immune system

Abstract: Ubiquitination is a post-translational modification process that has been implicated in the regulation of innate and adaptive immune responses. There is increasing evidence that both ubiquitination and its reversal, deubiquitination, play crucial roles not only during the development of the immune system but also in the orchestration of an immune response by ensuring the proper functioning of the different cell types that constitute the immune system. Here, we provide an overview of the latest discoveries in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
169
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(179 citation statements)
references
References 207 publications
2
169
1
Order By: Relevance
“…75 Ubiquitin is a highly conserved polypeptide with 76 amino acids with the property of reversible posttranslational modification. 76 Ubiquitination of proteins occurs in host cells in order to sort the proteins for degradation as well as for other cellular processes. Usually, the 26S proteasome machinery carries out ubiquitination of proteins.…”
Section: Manipulation Of Host Cellular and Subcellular Targets By E mentioning
confidence: 99%
“…75 Ubiquitin is a highly conserved polypeptide with 76 amino acids with the property of reversible posttranslational modification. 76 Ubiquitination of proteins occurs in host cells in order to sort the proteins for degradation as well as for other cellular processes. Usually, the 26S proteasome machinery carries out ubiquitination of proteins.…”
Section: Manipulation Of Host Cellular and Subcellular Targets By E mentioning
confidence: 99%
“…Following secretion, these cytokines prime other immune cells to prepare them for defense against microbial infections. Given that the Ub system-mediated regulation of the TLR, RLR and TNF-α signaling pathways has been well documented in several previous reviews, 12,14 we will focus our discussion on NLR signaling.…”
Section: Modulation Of Innate Immune Signaling By the Ubiquitin Systemmentioning
confidence: 99%
“…In addition to protein degradation, ubiquitination has also been directly involved in various cellular signaling events, including DNA damage repair [3], immunity [4][5][6], T-lymphocyte control [7], and cell division [8,9]. Recent progress in ubiquitin biology revealed that various forms of unanchored ubiquitin are also involved in cellular signaling [10][11][12].…”
Section: Introductionmentioning
confidence: 99%